Religiusitas sebagai Strategi Internal Public Relations untuk Meningkatkan Loyalitas Anggota Koperasi Syariah - Rizky Estu Handayani; Nila Nur Azizah; Luhur Prasetiyo (Journal of Economics, Law, and Humanities, 2025)
Sharia-based Savings and Loan Cooperatives (KSPPS) face significant challenges in maintaining institutional sustainability, making internal public relations strategies essential for strengthening employee loyalty. This study aims to analyze the role of religiosity as an internal public relations strategy in fostering employee loyalty at KSPPS Tunas Arta Mandiri Syariah KC Magetan. This research employs a qualitative approach and a case study method in its field research. Primary data were collected through observation and in-depth interviews with leaders and employees at the research site, while secondary data were obtained from institutional documents. Data were gathered using participatory observation, semi-structured interviews, and documentation. The data analysis procedures consisted of data reduction, data display, and conclusion drawing. The findings reveal that religiosity, integrated into the organizational culture through routine activities such as Yasin recitation, sholawatan, morning prayers, daily evaluations, and social programs, positively influences employee motivation, internal communication quality, and sense of belonging. The application of the core values of tauhid, amanah, and manfaat as the foundation of the work culture further strengthens employees’ emotional attachment to the institution. This study concludes that consistently applied religiosity within internal public relations strategies not only enhances work quality but also serves as a key factor in building employee loyalty, thereby supporting the sustainability of KSPPS.